2019
DOI: 10.1155/2019/6289478
|View full text |Cite
|
Sign up to set email alerts
|

Potential Association of Body Constitution with the Prognosis of IgA Nephropathy: A Long-Time Follow-Up of 203 Cases in China

Abstract: Objective. This study investigated the association between body constitution (BC) and the prognosis of IgA nephropathy. Methods. We analyzed 203 biopsy-diagnosed IgA nephropathy patients, who were followed up for (63.9±16.2) months. The participants’ BC statuses were evaluated with the Constitution in Chinese Medicine Questionnaire; the relationships between clinical parameters and renal outcomes were analyzed by Cox regression. Results. Patients were classified into chronic kidney disease stages with 43.4% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Previous studies have investigated the association of TCM body constitution with various diseases and conditions, such as coronary artery disease [4], type 2 diabetes [5], metabolic syndrome [5], IgA nephropathy [6], obesity [7], and cancer-related fatigue [8]. In addition, a recent review study based on five electronic literature databases, in both English and Chinese, identified 1639 clinical studies that evaluated the association between TCM body constitutions and various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the association of TCM body constitution with various diseases and conditions, such as coronary artery disease [4], type 2 diabetes [5], metabolic syndrome [5], IgA nephropathy [6], obesity [7], and cancer-related fatigue [8]. In addition, a recent review study based on five electronic literature databases, in both English and Chinese, identified 1639 clinical studies that evaluated the association between TCM body constitutions and various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][16][17][18] With the damaged degree of pathological damage in IgAN patients increases gradually, TCM syndrome manifests changes from deficiency qi and yin to deficiency yin of liver and kidney, and then deficiency yang of spleen and kidney. [19][20][21] Besides, the stasis syndrome and rheumatism syndrome are significant comorbidities in the process of IgAN chronic progression. [18] The characteristics of TCM treatment for IgAN are mainly composed of tonic deficiency medicines, supplemented by blood-activating and stasis-eliminating medicines, heat-clearing medicines, inducing diuresis and excreting dampness medicines, and astringent medicines to combine with formulas.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Many studies used Lee's grading system and Katafuchi score system to classify the severity of glomerulus and tubulointerstitial lesions of IgAN and then to investigate the relationship between renal pathological classifications and TCM syndromes. [20][21] It is reported that the pathological change of IgAN patients with the spleen and kidney yang deficiency syndrome was the most serious, and follow by the liver and kidney yin deficiency syndrome. [22] For IgAN patients with Lee's grade above, conventional treatment is nourishing yin of liver and kidney or nourishing yang of spleen and kidney.…”
Section: Theoretical Basis Of Iga Nephropathy Treated By Traditional Chinese Medicinementioning
confidence: 99%
“…Primary immunoglobulin A nephropathy (IgAN) is one of the most common glomerular diseases in children and teenagers and is mainly characterized by proteinuria, filtration membrane injury, and glomerulonephritis (1,2). In China, the development of IgAN is the major cause of end-stage kidney diseases (3)(4)(5). Delayed or inappropriate treatment of patients with IgAN in the early stage resulted in permanent disability in approximately 30% of these patients (4,6).…”
Section: ' Introductionmentioning
confidence: 99%
“…In China, the development of IgAN is the major cause of end-stage kidney diseases (3)(4)(5). Delayed or inappropriate treatment of patients with IgAN in the early stage resulted in permanent disability in approximately 30% of these patients (4,6).…”
Section: ' Introductionmentioning
confidence: 99%